Eight-grade English textbooks evaluation in Tegal, Central Java - Raksi Hajar Prawestri (Universitas Sarjanawiyata Tamansiswa, 2019)
This research is aimed at measuring whether the three books used in the secondary schools in Tegal i.e â€œMandiri: Practise Your English Competenceâ€, â€œInteractive English 2â€, and â€œNew Headwayâ€ are right or not, and revealing the strength and weaknesses of the three books based on the theories of excellent textbook developed by the researcher based on the Tomlinsonâ€™s (2003) framework. This research is evaluation research. The data were collected through observation, questionnaire, and document analysis. The data were analysed using Miles, Huberman, and Saldana's flow model of qualitative data research, which includes data collection, data reduction, data display, and giving the conclusion. The study found out that â€œMandiri: Practise Your Sentence